Certification study guide series IBM Tivoli Federated Identity Manager 6.1. - B(uml)ucker, Axel.; Abebe, Azania; Benavides, George; Safari eBooks ([Poughkeepsie, N.Y.?] : IBM, 2009)
"This IBM Redbooks publication is a study guide for the "IBM Certified Deployment Professional - IBM Tivoli Federated Identity Manager V6.1" certification test, test number 000-891, and is meant for those who want to achieve IBM Certifications for this specific product. The IBM Tivoli Federated Identity Manager Certification, offered through the Professional Certification Program from IBM, is designed to validate the skills required of technical professionals who work with the implementation of the IBM Tivoli Federated Identity Manager Version 6.1 product"--Resource description page.
Certification overview -- Planning -- Installation and configuration -- Test and validation -- Troubleshooting.
Title from resource description page (viewed Mar. 5, 2010).
"SG24-7783-00"--Resource description page.
Includes index.
Keywords: IBM Tivoli identity manager -- Certification -- Study guides; Electronic commerce -- Security measures -- Study guides; Business -- Data processing -- Security measures -- Study guides; Computer networks -- Access control -- Study guides; Computer security -- Study guides; Electronic books